Avaliação do planejamento do transporte ferroviário regional de carga: análise para o semiárido brasileiro sob os aspectos do crescimento e desenvolvimento econômico regional - Silva, Erika Vanessa Alves da (2017)
Several theories have shown a positive relationship between investment in cargo transportation and the promotion of economic growth, especially for developing countries. In this sense, it is intended to deepen the discussion towards the relationship of rail freight and determining factors of regional economic development. The general objective of this work is to propose an instrument to evaluate the planning and operation of a regional railway infrastructure of cargo in the Brazilian semi-arid region, under the regional economic development aspects. For this, the proposed method is configured in an iterative process composed of four steps. The applicability of the proposal was tested and evaluated from a case study involving the Transnordestina railway. Among the main results are the proposal and measurement of the variables municipal GDP, trade balance, number of jobs related to the railway sector and Firjan index of municipal development as economic and social indicators that relate regional rail infrastructure to regional development. Another important result was the mapping of the potential load demand and determination of the radius of influence of the railroad over the region in which it will be inserted. Finally, the method proved efficient in its theoretical proposition and application to the Transnordestine railway.